Analisis Kebijakan Penerapan Tingkat Komponen Dalam Negeri (TKDN) dalam Pengadaan Barang dan Jasa di Kementerian Pendidikan, Kebudayaan, Riset, dan Teknologi: Studi Kasus di Biro Umum dan Pengadaan - Taufik Hidayat; Roni Ekha Putera; Hendri Koeswara (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2024)
This research aims to describe and analyze the application of the Domestic Component Level (TKDN) in the procurement of government goods and services at the General Bureau and Procurement of Goods and Services of the Ministry of Education, Culture, Research and Technology as well as determine the level of success and find a model for implementing the Domestic Component Level (TKDN) policy in the procurement of government goods and services at the General Bureau and Procurement of Goods and Services of the Ministry of Education, Culture, Research and TechnologyThe research method used is a descriptive analytical method with a qualitative approach. Data was collected through in-depth interviews with relevant officials, document analysis, and direct observation of the goods and services procurement process. This research identified several main challenges in implementing TKDN, including limited local production capacity, quality of domestic products, and understanding and compliance with TKDN regulations by procurement actors. The research results show that although the TKDN policy has great potential to encourage local industry, its implementation still faces various obstacles. Efforts are needed to increase the capacity and quality of domestic products, as well as more intensive outreach and training for procurement actors. This research recommends increasing coordination between government and industry, as well as regular evaluation of TKDN policies to ensure their effectiveness in supporting national economic development.